Effectiveness and Tolerability of a New Formulation of a Topical Anesthetic in Reduction of Pain and Parents' Satisfaction in Pediatric Dentistry - Gianmaria Fabrizio Ferrazzano; Giuseppe Di Fabio; Roberto Gatto; Sara Caruso; Gianluca Botticelli; Silvia Caruso (MDPI AG, 2023)
The aim of the present study was to test a new topical anesthetic gel with a different formulation (10% lidocaine, 10% prilocaine) to analyze its effectiveness in pain control, during the subsequent injection of local anesthetic, and the presence of any side effects. Methods: The study's research design was a randomized controlled clinical trial on 300 children, aged 5-8 years, divided into two groups, each of 150 patients, according to pre-injection procedures (presence or absence of topical anesthesia). The injection pain was analyzed using the Wong-Baker Faces Pain Rating Scale (PRS) and the Face, Legs, Activity, Cry, Consolability Scale (FLACC). At the end of the procedures, patients' parents' satisfaction was recorded. The data were analyzed using the Student's T test, Mann-Whitney U test and Chi-square test. Results: There were statistically significant differences between the two groups both in the PRS and FLACC ratings. Both in subjective and objective pain evaluations, significantly higher pain ratings were observed in the group without topical anesthesia. There was also a statistically significant difference in terms of patients' parents' judgment, as in the group with the use of topical anesthetic the level of parental satisfaction is statistically higher. Conclusion: The experimental anesthetic has proved very effective in its use as a topical gel in both pain measurement scales, thus validating its use on the oral mucosa, for its pharmacological and psychological effect, in the total absence of local and systemic side effects.